The Influence of Competence and Work Discipline on Employee Performance with Motivation as an Intervening Variable : Study at PT Jateng Argo Berdikari (Perseroda) - Fernanda Nasrullah; Endang Tjahjaningsih (International Journal of Economics and Management Research, 2025)
The most crucial factor in achieving employee performance targets and producing high-quality work lies in how a company fosters motivation among its employees. Motivation serves as a driving force that influences employees’ willingness to perform their tasks optimally. This study employed a quantitative research approach using primary data. The research population consisted of 381 employees of PT Jateng Agro Berdikari (Perseroda), with performance appraisal conducted through the 360-Degree Feedback method. The sampling technique applied was purposive sampling, selecting respondents who met specific research criteria. Data collection was carried out through questionnaires and interviews to ensure a comprehensive understanding of the research variables. Instrument validity and reliability tests were conducted to confirm that the measurement tools used were both accurate and consistent. Data analysis involved multiple linear regression to determine the relationships between variables, while hypothesis testing utilized partial tests (t-tests), the coefficient of determination (R²), path analysis, and the Sobel test to examine mediation effects. The results showed that competence and work discipline significantly influenced work motivation. However, competence alone did not have a direct impact on employee performance. In contrast, work discipline and work motivation had a positive and significant effect on employee performance. Moreover, work motivation was found to mediate the relationship between competence and employee performance, as well as between work discipline and employee performance. These findings highlight the importance for companies to develop strategies that not only enhance employees’ competencies and enforce work discipline but also strengthen work motivation. A motivated workforce is more likely to achieve performance targets and maintain high standards of work quality, thereby supporting organizational success and sustainability.